The effect of Clostridium difficile infection on the course of liver cirrhosis - A. A. Driga; M. V. Mayevskaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of investigation. To estimate the frequency of Clostridium difficile (C. difficile) infection and its effect on severity and pattern of complications at the compensated liver cirrhosis (LC). Material and methods. The original study included overall 47 patients with decompensated LC (Child-Pugh class B - 27 patients and class C - 20 patients). All patients underwent clinical interviewing with assessment of past history, daily blood pressure (BP) measurement with calculation of the mean blood pressure level, blood tests, ECG, abdominal ultrasound, esophagogastroduodenoscopy, echocardiography, chest X-ray, lactulose hydrogen breath test, Clostridium difficile ELISA stool test. Results. Clostridium difficile infection was found in 26 (55.3%) of 47 patients with decompensated LC. Of patients with alcoholic LC the mean Maddrey score in Clostridium difficile-infected subgroup was significantly higher than the score of non-infected patients. For the last 6 months prior to the study enrollment 50% of patients with Clostridium difficile infection were hospitalized and received antibiotics significantly more frequently. Metronidazole was prescribed more frequently to Clostridium difficile-infected patients (92.3% versus 9.5%; р